Study on microstructure and physical properties of composite films based on chitosan and methylcellulose - Pinotti, Adriana Noemi (2007)
Biodegradable films obtained from chitosan (CH) and methylcellulose (MC) can reduce environmental problems associated with synthetic packagings. Biodegradable films still need a cost reduction to be economically profitable; the use of CH, a by-product obtained from wastes of the fishing industry would be a good alternative. The objectives of the present work were to characterize physical, mechanical and water vapor barrier properties and microstructure of films of CH, MC and their mixtures. Solutions of 2% CH and 1% MC were mixed in different proportions. Films were obtained by casting. Film microstructure was characterized by SEM, X-ray diffraction and FTIR spectroscopy. Water vapor permeabilities for CH and MC films were 6.67±0.74×10−11 and 7.55±0.60×10−11 g/s m Pa, respectively; composite film permeabilities did not differ significantly from these values. CH films showed rigid characteristics (high elastic modulus and low elongation). Flexibility of composite films increased with increasing MC content, the higher elongation and lower elastic modulus of composite films indicated the relevance of hydrocolloid interactions.